2020
DOI: 10.1186/s13018-020-02000-1
|View full text |Cite
|
Sign up to set email alerts
|

Retraction Note: LncRNA TUG1 was upregulated in osteoporosis and regulates the proliferation and apoptosis of osteoclasts

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…LncRNA has been con rmed to play a vital role in bone metabolism diseases. Han et al revealed that downregulation of lncRNA TUG1 effectively inhibited osteoclast proliferation and might serve as a potential target for the treatment of osteoporosis [21]. Shen et al reported that lncRNA HOTAIR was highly expressed in osteoporosis patients, which prevented osteogenic differentiation by regulating Wnt/βcatenin pathway [22].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA has been con rmed to play a vital role in bone metabolism diseases. Han et al revealed that downregulation of lncRNA TUG1 effectively inhibited osteoclast proliferation and might serve as a potential target for the treatment of osteoporosis [21]. Shen et al reported that lncRNA HOTAIR was highly expressed in osteoporosis patients, which prevented osteogenic differentiation by regulating Wnt/βcatenin pathway [22].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of miR-214, miR-363-3p, and miR-142-5p accelerates PI3K/AKT signaling by targeting phosphatase and tensin homolog (PTEN), which is an inhibitor of PI3K [108][109][110][111]. In addition, the excessive expression of lncRNA-TUG1 also gives rise to downregulated PTEN, which may be relevant to the positive effect of TUG1 on osteoclastogenesis [112]. lncRNA-CRNDE also promotes osteoclast proliferation via the PI3K/AKT signaling pathway.…”
Section: Nf-κb and Relatedmentioning
confidence: 99%
“…Skeletal system diseases, including osteoporosis, osteoarthritis, and osteosarcoma, are related to the dysregulation of lncRNAs expression in cartilage and bone cells 9 . For example, lncRNA TUG1 was recently found to be up‐regulated in osteoporosis and regulated osteoclasts proliferation and apoptosis 10 . The lncRNA ORLNC1 could direct MSC fate and thereby regulating bone mass 11 .…”
Section: Introductionmentioning
confidence: 99%
“…9 For example, lncRNA TUG1 was recently found to be upregulated in osteoporosis and regulated osteoclasts proliferation and apoptosis. 10 The lncRNA ORLNC1 could direct MSC fate and thereby regulating bone mass. 11 The expression of lncRNA MSC-AS1 was increased during osteogenic differentiation and played as protective role in steoporosis.…”
Section: Introductionmentioning
confidence: 99%